The effects of laughter therapy on depression symptoms in patients undergoing center hemodialysis: A pragmatic randomized controlled trial. Issue 4 (25th August 2020) - Bennett, Paul N.; Hussein, Wael F.; Reiterman, Marc; Yu, Junhua; Schiller, Brigitte
Abstract: Introduction: People with end‐stage renal disease undergoing hemodialysis are at increased risk for stress, anxiety, and depression. The study objective was to measure the effect of intradialytic group laughter therapy on depressive symptoms in people on hemodialysis (HD). Methods: Pragmatic randomized controlled trial conducted with prevalent HD patients in 10 centers in Northern California. The intervention group received a once weekly, 30‐minute group laughter therapy session for 8 weeks. Primary outcome was the number of people with depressive symptoms as measured using the four Item Patient Health Questionnaire. Secondary outcomes were anxiety, subjective well‐being, and patient‐reported outcome measures. Findings: In all, 151 participants completed both predepression and postdepression symptom measures (72 intervention and 79 control). The proportion of patients with self‐reported depressive symptoms changed from 17 (22%) to 16 (20%), in the control and from 11 (17%) to 5 (8%) in the intervention arms, respectively (P = 0.04). In the control arm, 7 out of the 17 patients with self‐reported depressive symptoms at baseline continued to report depressive symptoms at follow up compared to the intervention arm where only 1 of 12 patients continued to report depressive symptoms. No differences were noted between the groups for reported anxiety, patient‐reported dialysis symptoms, and subjective well‐being. Discussion: This study found intradialytic group laughter can decrease the number of people with depressive symptoms receiving hemodialysis. Larger and long‐term studies are required to evaluate the effect of intradialytic laughter on patient related outcomes and quality of life.